A Matemática da música: uma abordagem para o ensino de frações através da teoria musical - Santos, Erick Quintino dos (2022)
This study presents a proposal based on the application of innovative methodologies through didactic sequences for the teaching of Mathematics to Elementary School II students. It aims to introduce concepts about fractions from the perspective of the relationship between ratios, in order to complement and deepen concepts on the subject, combined with the traditional form of presentation provided for in the National Curricular Parameters (PCN's) and in the National Common Curricular Base (BNCC) of Education Fundamental II, through practices related to Music and the study of the musical scale using new perspectives and methodologies that provide cognitive and socio-emotional structures for the teaching of Mathematics in a consistent and meaningful way, where it is expected that in this way students receive opportunities of new experiences during the didactic sequence so that they can implement and maintain learning throughout their lives, applying it in society as one of the guarantees that Education proposes to fulfill.